2019
DOI: 10.1021/acsaem.9b01550
|View full text |Cite
|
Sign up to set email alerts
|

Latest Designing Principle on the Microstructure and Lattice-Structure for High-Energy-Density Antiferroelectric Materials in Fast Discharging Applications

Abstract: Antiferroelectric (AFE) materials are considered to have a potentially ultrahigh energy density, which is a determinant for pulse capacitors used in the energy storage section of fast discharging applications. Optimization of the energy density in AFE materials has basically focused on the modulation of compositions or microstructure according to some empirical principles. An efficient, targeted, and in-depth designing strategy is always expected based on some distinct structure−property relationships. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…For low NN addition ( x ≤ 0.14), the dielectric loss significantly decreases so that the E b value continuously increases. However, with NN further increasing to x = 0.16, the increasing dielectric loss and increasing secondary phase content make the ceramics leaky, resulting in a lower E b value 42 . Therefore, x = 0.14 composition ceramics possess the largest E b value due to the lowest dielectric loss and appropriate secondary phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For low NN addition ( x ≤ 0.14), the dielectric loss significantly decreases so that the E b value continuously increases. However, with NN further increasing to x = 0.16, the increasing dielectric loss and increasing secondary phase content make the ceramics leaky, resulting in a lower E b value 42 . Therefore, x = 0.14 composition ceramics possess the largest E b value due to the lowest dielectric loss and appropriate secondary phase.…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, the BDS first increases with appropriate amount of NN content, from 12.62 kV/mm at x = 0 to 17.77 kV/mm at x = 0.14, and then, decreases to 16.04 kV/mm with a further addition of the NN content. Generally, the BDS is determined by a couple of factors, such as the microstructure, [37][38] conductivity mechanism, [39][40][41] secondary phase, 42 and extrinsic parameters. For BNT-BA-xNN ceramics, the variation of BDS with increasing NN content may be related to the evolution of dielectric loss and the content of secondary phase.…”
Section: Methodsmentioning
confidence: 99%
“…16 La 3+ was also reported to further stabilize the AFE order in Pb(Yb 1/2 Nb 1/2 ) 0.92 Ti 0.08 O 3 ceramics. 23 3.2.2 Electric field-induced polarization. The polarization response of the AFE ceramics to the first cycle of applied electric field is presented in Fig.…”
Section: Properties Of the Afe Ceramicsmentioning
confidence: 99%
“…13,14 However, the W rec of most lead-free ceramics is low. 15 In contrast, the higher energy density of PbZrO 3 (PZ) based AFE materials is more suitable for practical application. For instance, (Pb 0.98 La 0.02 )-(Zr 0.45 Sn 0.55 ) 0.995 O 3 ceramics exhibited a large W rec value (7.09 J/cm 3 ) and Huang et al also found that (Pb 0.91 Ba 0.045 La 0.03 )(Zr 0.6 Sn 0.4 ) ceramics reached an excellent W rec value (8.16 J/cm 3 ).…”
Section: Introductionmentioning
confidence: 99%